Effect of Extremely Low Frequency Electromagnetic Field on MAP2 and Nestin Gene Expression of Hair Follicle Dermal Papilla Cells. Issue 6 (June 2016) - Moraveji, Marzie; Haghighipour, Nooshin; Keshvari, Hamid; Abbariki, Tannaz Nourizadeh; Shokrgozar, Mohammad Ali; Amanzadeh, Amir
Introduction: In recent years, the extremely low frequency electromagnetic field (ELF-EMF) has attracted a great deal of scientific interest. The ELF-EMF signal is able to control ion transport across ion channels and therefore induce cell differentiation. Aim: The purpose of this study was to investigate the effect of ELF-EMF (50 Hz, 1 mT) on MAP2 and Nestin gene expression of dermal papilla mesenchymal cells (DPCs). Methods: In order to examine the effect of chemical and electromagnetic factors on gene expression, 4 experimental groups, namely chemical (cell exposure to chemical signals), EMF (exposing cells to ELF-EMF), chemical-EMF (subjecting cells to chemical signals and ELF-EMF) and control (with no treatment) groups, were prepared, treated for 5 days, and studied. To assess the effect of extended test time on the expression of neural differentiation markers (Nestin and MAP2), an EMF group was prepared and treated for a period of 14 consecutive days. The beneficial role of EMF in inducing neural differentiation was shown by real-time PCR analysis. Results: The higher expression of MAP2 after 14 days compared to that after 5 days and decrease of cell proliferation on days 5 to 20 were indicative of the positive effect of extending treatment time on neural differentiation by evaluation of gene expression in EMF group.